"Penrod" and the Perception of Characters in Blackface at UW-Eau Claire - Clark, Sam (My University, 2014)
The purpose of this study was to examine the multiple components of minstrel shows that were performed annually at the University of Wisconsin-- Eau Claire during the late 1920s and early 1930s, as well as other theatrical performances on campus featuring characters in blackface. This study also focused on the production of "Penrod," a play by Booth Tarkington performed by the campus group Strut and Fret during the 1933-34 school year, and examines how elements of minstrelsy contributed to the play's warm reception and overall success.
Color poster with text and photographs.
Keywords: Minstrel shows--University of Wisconsin--Eau Claire--1920s-1930s; Characters in blackface; Posters